Implementation of Internal Quality Assurance to Improve the Quality of Islamic Education - Indah Komsiyah (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to examine the implementation of internal quality assurance of madrasah Aliyah Amanatul Ummah International Standard to improve the quality of education as one of the international-based madrasah. There were 30 participants involved in this study, of consisted of 1 kiai, 1 madrasah head, 1 deputy coordinator of madrasah, 27 teachers (ustads). They were selected by using purposive sampling. This research was a case study research design with a single case study model in qualitative research. The qualitative data were collected by using observation, documents and interviews. The data analysis technique used three activity flows that occurred simultaneously, namely, l) data reduction; 2) data display, and 3) concluding/verification. The results of data analysis indicated that the quality assurance process has an orderly flow by Standard Operating Procedures. The process started from setting evaluation standards, implementing evaluations, monitoring, self-evaluation, auditing internal academic quality as a whole, formulating corrections, and improving quality. This cycle was carried out continuously. Quality assurance improved the quality of Islamic education. It had a positive impact on sustainable quality assurance and the commitment of stakeholders to achieve quality education